Parent-child interaction and adolescent misbehavior - Jamaluddin, Zakiyah (Penerbit Universiti Kebangsaan Malaysia, 2011)
Poor parental bond and control, poor parenting styles and poor familial environment quality have often been associated with adolescent misbehavior such as loitering, delinquency and juvenile crimes. Poor parental support and control have caused some resultant behaviors including aggressive behavior and substance abuse (Barber & Rollins 1990; Baumrind 1991; Maccoby & Martin 1983; Peterson & Rollins 1987; Rollins & Thomas 1979). Emotional bonding, support and proximity with parents in the course of childhood and adolescence have beneficial effects on psychological development. In addition, they provide an important protection against involvement in antisocial behavior (Barrera et al. 2001; Loeber 1990; Noller & Callan 1990). This was found consistent across cultures and across different social groups (Barber, 1992; Barrera et al. 2001; Brook et al. 1997). Emotional detachment or poor parental support however is associated to a certain amount of difficulties in adolescent development (Barrera & Li 1996; Rutter et al. 19980. Adolescents living in such a family context display personal difficulties and increased risks of developing deviant behaviors, such as aggression, vandalism, theft, alcohol and drug use ( Loeber & Stouthamer - Loeber 1998; Patterson et al. 1992). A study was conducted to evaluate parent-child interaction and its effect on adolescent misbehavior.